Red blood cell aggregation, disaggregation and aggregate morphology in autologous plasma and serum in diabetic foot disease - Sheremet’ev, Yury A.; Popovicheva, Aleksandra N.; Rogozin, Methun M.; Levin, Grigory Ya (Clinical hemorheology and microcirculation, 2019)
BACKGROUND: Diabetes mellitus is frequently associated with microcirculation pathology and hemorheological disorders. METHODS: 24 patients with diabetic foot and 22 healthy subjects were recruited. RBC aggregation, disaggregation and morphology of aggregates were determined in autologous plasma and serum. RESULTS: The RBC aggregation in patients with diabetic foot increased in autologous plasma and serum. Increased red blood cell aggregate strength in these patients was observed only in autologous plasma. Microscopic images of RBC aggregates of patients with diabetic foot show the formation of pathologic globular structures of aggregates in autologous plasma and serum. CONCLUSION: The RBC aggregation in autologous plasma and autologous serum in patients with diabetic foot is significantly higher than in healthy subjects. Increase in strength of RBC aggregates in diabetic foot patients was observed only in autologous plasma. The microscopic images of RBC aggregates in patients with diabetic foot indicate the formation of globular (pathologic) structures of aggregates in autologous plasma and serum. The differences in the morphology of RBC aggregates in autologous plasma and serum between healthy subjects and diabetic foot patients, obtained by microscopic image analysis with high magnification light microscope, can be used as an additional diagnostic tool in medical practice.